استعاذات معنویہ اور عصر حاضر میں ان کی اہمیت: Iste’azat e Ma’nwiyyah and Their Importance in Present Era (Al-Qamar, 2023)
The Holy Qurān provides guidance on all aspects of human life, it contains guidance on the reality of human life, good and evil, (Ḥalāl and Ḥarām), moral teachings on every aspect of life. Many people are those who deny the end of spirituality and many are convinced of materialism and those who believe in spirituality also have many ideas. One group of them has the point of view that the system of the universe is running according to nature and there is no effect or cause in it. But on the other hand, there is a group that believes in spirituality as well as the spirits in the world such as jinns, demons, ghosts, fairies, etc. Among the supernatural creatures mentioned in the Holy Qurān, there is mention of coming to the refuge of Allah Almighty from the evil of devils, jinn, whispers and magic. This refuge is generally described by the Book of Allah as Isti'aza. Because it has been instructed to seek refuge from the whispers and incitements of the devils, because the treatment of these temptations is only in the hands of Allah. The last chapter of the Qur'an (Al-Nās) was revealed only to seek refuge from the temptations of jinn and humans. And from this, in the first Surah (Al-Falq), it is recommended to pray to seek refuge with Allah from every evil. From the revelation of these two continuous Surahs (Al-Mu'awd'tain), it is known what place Ista'azah and Ta'awwuz have in religion. Therefore, the Research title is important from the Islamic point of view and contemporary requirements.
Keywords: Iste’azat e Ma’nwiyyah; Importance; Present era